Barriers to the access of people with disabilities to health services: a scoping review - Karina Aparecida Padilha Clemente; Simone Vieira da Silva; Gislene Inoue Vieira; Maritsa Carla de Bortoli; Tereza Setsuko Toma; Vinícius Delgado Ramos; Christina May Moran de Brito (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the scientific evidence regarding barriers to the access of people with disabilities to health services. METHODS A scoping review was carried out from the main question: "What are the main barriers that people with disabilities face in accessing health services?" The articles were surveyed in July 2019 in six scientific literature databases. Of the 1,155 documents identified in the searches, after selection by title and abstract, 170 publications were read in full and, thus, 96 articles were included and categorized according to the theoretical framework. RESULTS The main barriers indicated by the users of the service were: communication failure between professionals and patient/caregiver; financial limitations; attitudinal/behavioral issues; scarce service provision; organizational and transport barriers. The main barriers presented by service providers were: lack of training to professionals; failure of the health system; physical barriers; lack of resources/technology; and language barriers. CONCLUSIONS It was evident that people with disabilities face several barriers when trying to access the health services they need and that users and health professionals have distinct and complementary views on difficulties.